Somatic DNA hypomethylation in H. Pylori-Associated high-risk gastritis and gastric cancer: Enhanced somatic hypomethylation associates with advanced stage cancer - Leodolter, Andreas; Alonso, Sergio; González, Beatriz; Ebert, Matthias P.; Vieth, Michael; Röcken, Christoph; Wex, Thomas; Peitz, Ullrich; Malfertheiner, Peter; Perucho, Manuel (Clinical and Translational Gastroenterology, 2015)
OBJECTIVES: Helicobacter pylori-related high-risk gastritis (HRG) is a severe risk factor for gastric cancer (GC). The link between HRG and long-term risk for GC may involve genetic and epigenetic alterations underlying a field defect, i.e. a region of the mucosa prone to cancer development. Global DNA hypomethylation is a pervasive alteration in GC that associates with chromosomal instability and poor prognosis. The aim of this study was to determine the chronology of this alteration along the progression of HRG to GC, to test the hypothesis that it occurs early in the chronology of this pathway and plays a mechanistic role in the long-term cancer risk. METHODS: We comparatively measured the genomic methylation level in gastric biopsies from 94 GC patients and 16 of their cancer-free relatives, 38 HRG patients, and 17 GERD patients, using a quantitative enzymatic method. RESULTS: GC biopsies were hypomethylated compared to their matching non-tumor mucosa (P = 9.4 × 10- 12), irrespective of the tumor location or patients' country of origin. Genome-wide hypomethylation was also found in gastric mucosa of GC (P = 1.5 × 10-5) and HRG (P = 0.004) patients compared with healthy donors and GC relatives, regardless of the biopsy location within the stomach or previous H. pylori eradication therapy. An enhanced hypomethylation, distinguished by a bi-slope distribution of the differences in methylation between tumor and normal tissues, associated with a more invasive (P= 0.005) and advanced stage (P = 0.017) type of GC. CONCLUSIONS: Universal DNA demethylation in normal gastric mucosa in GC patients appears sporadic rather than familial. Genomic hypomethylation in HRG possibly contributes to a field defect for cancerization that is not reversed by bacterial eradication. Enhanced somatic hypomethylation may stratify GC for prognostic purposes.
CRIS-Team Scopus Importer:2025-03-05